Social change and history : aspects of the Western theory of development - Nisbet, Robert A. (New York, NY : Oxford University Press, 1969)
Preface: The primary purpose of this book is to set forth the essential sources and contests of the Western idea of social development. The book is in large part historical, in smaller part analytical and critical. In the rather long final chapter I explore some of the difficulties which seem to me to arise in the study of social change when this study is made subject to the fundamental concepts of developmentalism.
Introduction -- 1: History and metaphor -- 2: Metaphor of growth -- Part 1: Civilization As Growth In Time: The Biography Of A Metaphor -- 1: Greeks -- 1: Being as becoming -- 2: Cycles of genesis and decay -- 3: Progress and degeneration -- 2: Christians -- 1: Augustinian metaphor -- 2: Repudiation of cycles -- 3: Historical necessity -- 4: Two cities: conflict and resolution -- 5: Progress and degeneration -- 3: Moderns -- 1: Metaphor as progress -- 2: Expansion of metaphor -- 3: Progress and degeneration -- Part 2: Theory Of Social Development -- 4: Theory of natural history -- 1: Nature versus convention --2: Natural versus conventional history -- 5: Theory of social evolution -- 1: Sources and contexts -- 2: Elements of social evolution -- 6: Comparative method -- 1: Ethnocentric foundations -- 2: historical roots -- 3: Three series -- Part 3: Persistence And Change -- 7: Persistence of metaphor -- 1: Cycle, epic, and progress -- 2: Neo-evolutionism -- 8: Reflections on a metaphor -- 1: Uses of Metaphor -- 2: Abuses of metaphor -- 3: Irrelevance of metaphor -- Notes and references -- Index.
Bibliographical references included in "Notes and references" (p. 305-328).
Keywords: Social change; Historical sociology